Additive-Driven Interfacial Engineering of Aluminum Metal Anode for Ultralong Cycling Life - Sonal Kumar; Prasad Rama; Gaoliang Yang; Wei Ying Lieu; Deviprasath Chinnadurai; Zhi Wei Seh (Nano-Micro Letters, 2022)
Highlights A unique electrolyte combination for rechargeable aluminum battery was fabricated using aluminum trifluoromethanesulfonate as the main salt and tetrabutylammonium chloride as an additive. The presence of additive activates the Al-anode surface toward plating/stripping and aids in the formation of a protective solid electrolyte interphase layer on the anode, resulting in a substantially suppressed anodic overpotential for 1300 cycles. The cheap, high flash point and non-corrosive nature of the electrolyte makes it commercially promising.